Career Paths and Talent Management: A Study on Postgraduate Studies of Finnish Engineers - Koivisto, Matti (International Journal of Advanced Corporate Learning (iJAC), 2025)
Tight competition for jobs and skilled professionals has increased the need for talent development among both employees and employers. Employees must take care of their own skills to secure their position in the labor market and companies, in turn, must develop both the skills of their current employees and to attract new professionals. This paper focuses on the talent development of Finnish engineers, and it especially analyzes when and to what kind of master’s programs they apply to during their careers. First, it explores the potential differences at the application ages of the undergraduates applying to master’s programs offered by universities and polytechnics (UAS). Second, it investigates variations between the engineering management programs and discipline-specific programs of the UASs. Findings of the study indicate that the age distributions for the master’s programs in universities and UASs differ significantly and the UASs programs seem to be an important form of education for engineers in employment. Results on different kinds of programs indicate that both engineering management and discipline-specific master’s programs will be needed also in the future to fulfill the different kinds of career paths of the engineers.